The Incidence of Superficial Scald in "Wujiuxiang" Pears (Pyrus Pyrifolia Cv. Wujiuxiang) during and after Controlled Atmosphere Storage. Issue 3 (3rd February 2016) - Li, Limei; Xia, Yufeng; Xu, Cailing; He, Jingang; Guan, Junfeng
Abstract: This work is aimed to assess the effect of the low temperature controlled atmosphere (CA) storage on reducing the incidence of fruit superficial scald in "Wujiuxiang" pears ( Pyrus pyrifolia cv. Wujiuxiang). We set up four low temperature CA storage conditions with pCO2 0.03 kPa, 1 kPa, 3 kPa, 5 kPa, respectively, under pO2 3 kPa, and a control under normal air conditions with pCO2 0.03 kPa, pO2 21 kPa. During the low temperature storage and its subsequent period on‐shelf, the incidence of superficial scald as well as the changes in fruit quality and biochemistry such as phenols, relative electrical conductivity, malondialdehyde, polyphenol oxidase and peroxidase activity were monitored and analyzed. Our results showed that low O2 is the most important factor contributing to the reduced incidence of superficial scald during the low temperature CA storage. However, pCO2 less than 3 kPa had no influence on the incidence of superficial scald but higher pCO2 over 3 kPa caused CO2 injury to the stored fruit. In conclusion, low pO2 and pCO2 less than 3 kPa under low temperature is likely the best CA conditions for reducing the incidence of superficial scald in "Wujiuxiang" pears. Practical Applications: Superficial scald, a fruit postharvest physiological disorder has caused a significant loss in the production of "Wujiuxiang" pear, a popular cultivar in China. It is reported that CA storage can reduce efficiently the incidence of superficial scald in apples during storage. This work shows that this is also the case for "Wujiuxiang" pear during and after storage. A low temperature CA storage condition with low pO2 3 kPa while pCO2 lower than 3 kPa is then proposed for application in the storage of this pear.